The use of gelatine in long‐term storage (up to 48 hr) at 5°C preserves the pre‐freezing and post‐thawing quality of brown bear sperm. (14th July 2016) - Lopez‐Urueña, E; Anel‐López, L; Borragan, S; Ortega Ferrusola, C; Manrique, P; de Paz, P; Anel, L; Alvarez, M
Contents: Sedimentation of spermatozoa occurs during long‐term liquid storage and this may produce deleterious changes. Our aim was to apply gelatine supplementation during long‐term pre‐freezing storage of bear sperm, applying final dilution and 6% glycerol at room temperature and cool in straws. We tested four models of sperm storage using a 1:1 dilution in TTF‐ULE‐Bear extender (TesT‐fructose‐egg yolk‐glycerol 6%): (i) second 1:1 dilution at room temperature (RT), cooling at 5°C in a tube and final dilution (100 × 10 6  sperm ml −1 ) (Standard); (ii) final dilution at RT and cooling in a tube (FD‐Tube); (iii) final dilution at RT and cooling in 0.25 ml plastic straw (FD‐Straw); and (iv) final dilution at RT in extender supplemented with 1.5% gelatine (Gelatine) and cooling in a 0.25 ml plastic straw. A Standard sample was stored at 5°C for 1 hr (Control); the rest of the samples (Standard, FD‐Tube, FD‐Straw, Gelatine) were stored for 24 or 48 hrs before freezing (100 × 10 6  sperm ml −1, glycerol 6%). The quality of the samples was assessed for motility by CASA, and viability (SYBR‐14/propidium iodide‐PI‐; VIAB), acrosomal status (PNA‐FITC/PI; iACR) and apoptotic status (YO‐PRO‐1/PI; YOPRO‐) by flow cytometry. At pre‐freezing, after 48 hr, Gelatine showed significantly higher viability (for VIAB and YOPRO‐) and progressiveness (PM, LIN and STR). At 48 hr, Gelatine showed similar YOPRO‐, iACR, LIN, STR and ALH respect to Control. At both 24 and 48 h post‐thawing, Gelatine sample had similar scores for YOPRO‐, iACR, LIN, STR, WOB and VIAB (only 24 hr) when compared with Control, and lower for TM, PM, rapidPM, VAP and ALH. No differences were found among others experimental groups with respect to Control. In conclusion, gelatine could be a suitable alternative to preserve the viability and progressive motility of brown bear ejaculates during long‐term pre‐freezing storage at 5°C.